Eco-Friendly Synthesis of Gold Nanoparticles Using Microcystis elabens for Enhanced Photothermal Therapy Applications - Yinchuan Wang; Yifan Bo; Jiacheng Chen; Zhanglong Li; Susu Liu; Changyuan Yu; Jiahui Liu; Shihui Wang (Materials Open)
This study presents a strategy for the green biosynthesis of gold nanoparticles (AuNPs) using extracts from Microcystis elabens (ME-AuNPs). The synthesized ME-AuNPs exhibit photothermal responsiveness under 808[Formula: see text]nm near-infrared (NIR) laser irradiation and maintain photostability even after four cycles of irradiation. Cellular uptake experiments confirmed the concentration-dependent internalization of ME-AuNPs by 4T1 cells. MTT assays demonstrated good biocompatibility of ME-AuNPs within an appropriate concentration range (0–100[Formula: see text] [Formula: see text]g/mL) in the absence of laser irradiation. Upon laser irradiation, substantial production of reactive oxygen species (ROS) is induced, promoting cell apoptosis and leading to a cell death rate of 91%. Furthermore, western blot and a series of fluorescence assays confirmed that the cytotoxic effect on cancer cells is mediated through the apoptotic pathways involving caspase 3 and Bax/Bcl-2. In conclusion, our synthesized ME-AuNPs possess favorable photothermal conversion characteristics, demonstrating excellent therapeutic efficacy and safety.